2017
DOI: 10.1103/physreve.96.063112
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent direction reversals of moving spatially localized turbulence observed in two-dimensional Kolmogorov flow

Abstract: We have found that in two-dimensional Kolmogorov flow a single spatially-localized turbulence (SLT) exists stably and travels with a constant speed on average switching the moving direction randomly and intermittently for moderate values of control parameters: Reynolds number and the flow rate. We define the coarse-grained position and velocity of an SLT and separate the motion of the SLT from its internal turbulent dynamics by introducing a co-moving frame. The switching process of an SLT represented by the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…This advection effect disturbs an efficient supply of kinetic energy for disturbances to grow. This interpretation is consistent with the fact that the tails of SLT do not develop for large U y flows [43,44]. These kinds of effects can be seen in wallbounded flow but not be controlled.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This advection effect disturbs an efficient supply of kinetic energy for disturbances to grow. This interpretation is consistent with the fact that the tails of SLT do not develop for large U y flows [43,44]. These kinds of effects can be seen in wallbounded flow but not be controlled.…”
supporting
confidence: 86%
“…Kolmogorov flow is used to obtain many characteristics of solutions of Navier-Stokes equation and as a test field of novel idea of understanding complex solutions [38][39][40][41]. Recently, solutions in which spatially-localized chaotic regions and steady regions coexist were found even in 2D Kolmogorov flow [42][43][44].…”
mentioning
confidence: 99%
“…(2015 b ) demonstrated that such a first Fourier mode slice can be used to reduce the translation symmetry of the flow for all dynamics of interest. Later, the method was adapted successfully to two-dimensional Kolmogorov flows (Farazmand 2016; Hiruta & Toh 2017) and three-dimensional pipe flows (Willis, Short & Cvitanović 2016; Budanur et al. 2017; Budanur & Hof 2018); see Budanur, Borrero-Echeverry & Cvitanović (2015 a ) for a pedagogical introduction.…”
Section: Symmetries and Symmetry Reductionmentioning
confidence: 99%